2021
DOI: 10.1136/bmjopen-2020-042435
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and prediction models for acute aortic dissection: a systematic review

Abstract: ObjectiveOur study aimed to systematically review the methodological characteristics of studies that identified prognostic factors or developed or validated models for predicting mortalities among patients with acute aortic dissection (AAD), which would inform future work.Design/settingA methodological review of published studies.MethodsWe searched PubMed and EMBASE from inception to June 2020 for studies about prognostic factors or prediction models on mortality among patients with AAD. Two reviewers independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…For a long time, AD mortality rates and adverse events have been widely published as key indicators for evaluating surgical outcomes [ 6 8 ]. Patient reported outcomes (PROs) are emerging as an important component for patient care in cardiovascular diseases and have been reported to be critical as clinical assessments in the evaluation of treatment outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, AD mortality rates and adverse events have been widely published as key indicators for evaluating surgical outcomes [ 6 8 ]. Patient reported outcomes (PROs) are emerging as an important component for patient care in cardiovascular diseases and have been reported to be critical as clinical assessments in the evaluation of treatment outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…were observed in several studies that elevated D-dimer levels were associated with early mortality and postoperative compliactions (34,35). Admission D-dimer levels (>6.10 mg/ ml) were associated with an increased risk of in-hospital death (19). The D-dimer level in patients with AAD was in uenced by dissection type.…”
Section: Discussionmentioning
confidence: 93%
“…We retrospectively reviewed the medical records of the patients according to ID from our electronic database by two doctors ( Yansong Xu, Zheng Liang). Based on the current literature (19,20), we selected the following variables: Baseline characteristics, clinical features, laboratory results, imaging procedures, and outcomes of the patients. The baseline DLR was measured by dividing the D-dimr to the lymphocyte counts.…”
Section: Data Extraction and Variable Screeningmentioning
confidence: 99%
“…Recently, a systematic review of prediction models for acute aortic dissection concluded that the sample size varied from 35 to 1034 (median 165, IQR,103–348). 17 Tolenaar et al used multinational data from the International Registry of Acute Aortic Dissection (IRAD) that involved 1034 patients, but their aim was to investigate predictors of mortality among patients presenting with acute type B aortic dissection. 6 Czerny et al developed the German Registry of Acute Aortic Dissection Type A (GERAADA) score with 2537 patients involved, but the endpoint of their study was the 30-day mortality rate, and the patients who were diagnosed all underwent surgery, which is not suitable to use in ED.…”
Section: Discussionmentioning
confidence: 99%